The management and prognosis of patients with hepatocellular carcinoma: what has changed in 20 years?. (12th October 2015) - Yim, Sun Young; Seo, Yeon Seok; Jung, Chang Ho; Kim, Tae Hyung; Lee, Jae Min; Kim, Eun Sun; Keum, Bora; Jong, Young Kul; An, Hyunggin; Kim, Ji Hoon; Yim, Hyung Joon; Kim, Dong Sik; et al.
Abstract: Background & aims: There has been remarkable progress in the management of hepatocellular carcinoma (HCC) during the last several decades, but its effect on the prognosis of HCC patient needs clarification. We analysed the changes that affected prognosis of HCC patients diagnosed over two different eras. Methods: A retrospective study of 1318 patients diagnosed with HCC from 1986 to 2012 was conducted. Analysis was done according to two cohorts, cohort 1 (patients diagnosed with HCC from 1986 to 1992) and cohort 2 (patients diagnosed from 2006 to 2012). Results: Hepatitis B virus was the most common cause of liver disease for both cohorts (66.2% and 66.0%). The proportion of patients with Barcelona Clinic Liver Cancer stage 0/A was significantly lower in cohort 1 than in cohort 2 (14.4% vs. 39.5%, P < 0.001). The proportions of patients diagnosed during surveillance and general health check‐up were significantly higher in cohort 2 than in cohort 1 (28.6% vs. 10.6% and 26.3% vs. 7.9%, respectively) while those diagnosed during symptomatic evaluation was significantly higher in cohort 1 than in cohort 2 (45.1 vs. 81.4%, P < 0.001). Surgical resection rate was similar between the two cohorts (26.1% vs 26%) while the transcatheter arterial chemoembolization rate which was the highest in cohort 1 (40.6%) was overtaken by radiofrequency ablation in cohort 2 (55%) at BCLC stage 0/A. Median survival duration in cohort 2 was significantly longer than cohort 1 (65.0 vs. 7.9 months, P < 0.001). Conclusions: Implementation of national cancer surveillance and the advancement of treatment modalities have likely led to early detection of HCC and improvements in prognosis over the last 20 years.